The Efficacy of Vocational Skills- Based Training Program for People with Intellectual Disabilities at the Stage of Vocational Rehabilitation - AbdelAziz Sartawi; Owaisha Al Muhairy; Yasser Al Natour; Rawhi M. Obaidat (Sultan Qaboos University, 2016)
This study targeted investigating the efficacy of a vocational skill- based training program for people with intellectual disabilities. The program was set forth by the Department of Welfare and Rehabilitation of Persons with Disability, Ministry of Social Affairs (2009) at UAE. Subjects were 10 male individuals, age 15-20, with intellectual challenges who receive vocational training in Dubai Rehabilitation Center, UAE and who had an IQ score of 55-69 on Wechsler Adult Intelligence Scale (The Emirati Version). A control group was also recruited for the purpose of comparison (n=10). The Vocational Skill Scale as introduced by the investigators and was conducted before then after 8 weeks of the initiation of the training program in the academic year 2012/2013. Results showed significant differences between the scores obtained by the experimental group pre and post training, whereas there were no significant differences in the control group. The investigators recommended generalizing the vocational training program across centers of intellectual disability rehabilitation and expanding the program to include personal and social skill in addition to implementing the kills in a real work setting.